The Influence of Emotional Intelligence on Student Self-Efficacy Moderated by Religious Education in Islamic Schools - Khasanah, Yahya Fadhilatun; Shodiq, Sadam Fajar (Universitas Muhammadiyah Metro, 2024)
This study investigated the impact of Emotional Intelligence on students' Self-Efficacy, with Religious Education as a moderating factor in an Islamic school. The study involved two hundred and five twelfth grade students from science, social studies, and religion majors at MAN one Bantul High School, Yogyakarta, Indonesia. The sample was drawn using random sampling technique, so that each student had an equal chance of being selected as a respondent. This method was chosen to ensure fair and unbiased representation in the study, in order to obtain more accurate results regarding the effect of emotional intelligence on student self-efficacy moderated by religious education. by using the PLS-SEM method for data analysis. The results showed that Emotional Intelligence has a good and substantial impact on students' Self-Efficacy. Religious Education plays a moderating role in the relationship, increasing students' confidence in their talents. The importance of fostering emotional intelligence in education, particularly in Islamic institutions, is to improve students' self-efficacy and deepen their understanding of religious education.